Use of a trigger tool to identify adverse drug events in dogs - Fonseca, Beatriz Cristina De Oliveira; Forgerini, Marcela [UNESP]; Zorzin, Leila Crystina Dias; Martins, Marcelo Rodrigues; Matroianni, Patrícia De Carvalho [UNESP]; Lopes, Ângela Ferreira; Cunha, Paulo Henrique Jorge Da; Dewulf, Nathalie De Lourdes Souza (Revista Brasileira de Medicina Veterinaria, 2020)
Background: The highlight of the shortcomings in the regulation and surveillance of veterinary drugs in Brazil is the absence of a system to report adverse drug events (ADEs). Objective: Evaluate the use of triggers in dogs to detect ADEs by estimating the prevalence of ADE and identifying the possible triggers. Method: We screened medical records for ADEs and degree of harm caused by an ADE, using known triggers, with the Global Trigger Tool: Translated, adapted and validated for use in animal health. The triggers comprised two-fold increase in blood urea nitrogen or serum creatinine levels compared to baseline, administration of Vitamin K, administration of diphenhydramine or promethazine, excessive sedation or hypotension, administration of an antiemetic, abrupt cessation of medication, or others. The association between the occurrence of ADEs and variables, such as age, race, duration of hospitalization, polypharmacy, and clinical outcome was evaluated. Results: 148 medical records were analyzed. The trigger tools identified the known triggers 109 times in 68 medical records. Additionally, 14 ADEs were identified; the prevalence of ADEs was 9.5%. Positive predictive values of the triggers were 12.8%, and Vitamin K administration had the best performance. The duration of hospitalization (p-value = 0.030) and polypharmacy (p-value < 0.001) were associated with the occurrence of ADEs. Conclusion: Approximately 46% of the hospitalized dogs presented with at least one trigger. One out of five hospitalized dogs suffered from temporary harm due to an ADE. The duration of hospitalization and polypharmacy were found to be risk factors for ADEs in dogs.
Keywords: Drug safety; Patient safety; Triggers; Veterinary drugs; Veterinary pharmacovigilance